From ORFeomes to Protein Interaction Maps in Viruses - Uetz, Peter; Rajagopala, Seesandra V.; Dong, Yu-An; Haas, Jürgen

(untitled) (Genome Research, 2004)
Although cloned viral ORFeomes are particularly well suited for genome-wide interaction mapping due to the limited size of viral genomes, only a few such studies have been published. Here, we summarize virus interaction mapping projects involving vaccinia virus, hepatitis C virus (HCV), potato virus A (PVA), pea seed-borne mosaic virus (PSbMV), and bacteriophage T7, as well as some projects in progress. The studies reported suggest that virus-specific coding and replication strategies must be taken into account to yield accurate numbers of protein interactions. In particular, the number of false negatives can be significant for RNA viruses expressing precursor polyproteins (because interactions between full-length mature proteins are often not detected due to incorrect processing) and for viruses replicating in the cytoplasm whose transcripts have not been selected for splicing signals. In conclusion, the studies on viral protein interaction maps suggest that cloned pathogen ORFeomes will contribute to a holistic picture of the pathogenesis of infectious diseases and are ideal starting points for new approaches in systems biology. Both viral ORFeome and interaction mapping projects are being documented on our Web site (http://itgmv1.fzk.de/www/itg/uetz/virus/).